IRON DEFICIENCY WITHOUT ANEMIA IN COPD PATIENTS: ASSESSING EXERCISE CAPACITY AND EXACERBATION FREQUENCY - Abbasi, Munir Ahmad; Aamir Nazir; Sadaf Anwar Qureshi; Nadia Haleem; Naheed Khattak; Muhammad Adnan Rashid; Saima Iltaf (Journal of Ayub Medical College Abbottabad, 2024)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a global health challenge with significant morbidity and mortality. Iron deficiency, including non-anaemic iron deficiency (NAID), has been identified as a potential comorbid in COPD, affecting patient outcomes and disease severity. This study aimed to investigate the prevalence and impact of iron deficiency on the severity and clinical outcomes in COPD patients. Methods: In this descriptive cross-sectional study, 289 individuals diagnosed with COPD were enrolled and underwent comprehensive medical assessments, including haematological tests and spirometry from December 2019 to December 2023. The study focused on measuring iron levels, exercise capacity, and exacerbation frequency, comparing iron-deficient and non-iron-deficient groups. Results: The study found that 46.7% of participants had iron deficiency. Those with iron deficiency showed significantly lower exercise capacity as measured by the six-minute walk distance and experienced a higher frequency of yearly COPD exacerbations. However, no significant differences were observed in airflow limitation and the overall quality of life between the iron-deficient and non-iron-deficient groups. Conclusion: The findings suggest that iron deficiency, particularly NAID, is associated with a more severe progression of COPD, characterized by reduced exercise capacity and increased exacerbation frequency. These results highlight the importance of considering iron deficiency in the management of COPD to potentially improve patient outcomes. Keywords: Chronic Obstructive Pulmonary Disease (COPD); Iron Deficiency; Non-Anaemic Iron Deficiency (NAID); COPD Exacerbations; Exercise Capacity in COPD; COPD Management Strategies